TORAKOCHIRURGIANuss method in treatment of asymmetric and mixed chest wall deformity - Korlacki, Wojciech; Grabowski, Andrzej; Dzielicki, Józef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : In 1998 Donald Nuss proposed MIRPE. It was designed for symmetric PE being not so suitable for asymmetric or compound ones. Aim : The paper aim was to present own 12-year experience in repair of asymmetric or compound chest deformity based on MIRPE technique but with necessary completions. Material and methods : 108 patients with asymmetric or compound type of chest wall deformity were operated in the study group. There were 99 men and 9 women in age from 10 to 26 years (average 16.8 years). All patients were operated on according to MIRPE with additional procedures: two bars installation, excising of eminent parasternal parts of ribs, sternum transversal incision. Results : There were no deaths. Postoperative complications were noted in 8 (7.4%) patients. The operative time ranged from 55 to 130 minutes (average 95 minutes). The hospital stay ranged from 4 to 12 days (average 5.3 days). In 86 (79.6%) of the patients an adequate contour of the anterior chest wall has been gained after the primary procedure. In 18 patients (16.6%) the additional correction was performed in the time of bar removal. 4 patients refused next correction. Conclusions : Patients over 15 years of age with an asymmetric or compound deformity are the vast group in need of correction. Additional procedures to achieve a comprehensive correction of the deformity were successfully introduced. Combining MIRPE with the open procedures does not change the postoperative course of patients. Recent results and forward clinical observations may give proof to establish MIRPE linked with proper open procedures as a method of choice in asymmetric or mixed funnel chest correction.